Pengaruh Waktu Perendaman dalam Larutan Ca (Oh)2 0,5% terhadap Karakteristik Keripik Singkong - Aghnia Rahmawati; Hendrawan Hendrawan; Cucu Maryani (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2022)
Cassava (Manihot Utilissima Pohl) is one of the food crops that is quite high in production but is easily damaged. Cassava as a raw material for chips has a weakness, namely it contains a bitter or astringent taste, and after being fried, the texture becomes hard. In addition, during the processing before frying there will be a browning reaction due to the reaction between sugar and protein or amino acids. Soaking cassava in a solution of whiting is an effort to reduce the astringent or bitter taste, improve the texture of the cassava chips to make them more crispy, and prevent the browning reaction. This study aims to determine the effect of the immersion period of cassava slices in 0.5% (Ca(OH)2) solution on several characteristics of the cassava chips produced. The design used was a randomized block design (RAK) with 6 treatment periods of immersion (6 hours, 12 hours, 18 hours, 24 hours, 30 hours and 36 hours) with a concentration of 0.5% Ca(OH)2 solution (w/v). ) and repeated 4 times. Organoleptic testing of color, taste, aroma and crispness was carried out by acceptance test (Hedonic). The results showed that soaking cassava in a 0.5% Ca(OH)2 solution for 30 hours produced cassava chips with the best characteristics based on the assessment of taste, aroma, color and crispness.